Is vegetarianism related to anxiety and depression? A cross-sectional survey in a French sample - Laurent Bègue; Rebecca Shankland (BMC, 2022)
Abstract Objective The relationship between vegetarianism and mental health is controversial. The aim of the present study is to examine the cross-sectional association between anxiety, depression, and vegetarianism in a French sample while controlling for potential confounders. Design Self-reported questionnaire data were obtained from a large cross-sectional sample. Participants and setting We included an online sample of 6578 participants aged 18-90, 70.8% females. Results Analyses of variance with age, gender, body mass index (BMI), educational level, monthly income, and city size as covariates showed that vegetarians and non-vegetarians did not appear to have significantly different levels of anxiety or depression. Conclusion Our findings do not suggest a link between plant-based diet and anxiety or depression, either before or after adjustment for relevant factors.